2010
DOI: 10.2176/nmc.50.1079
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Lymphoproliferative Disorders of the Central Nervous System After Kidney Transplantation: Single Center Experience Over 40 Years -Two Case Reports-

Abstract: Further reduction of mycophenolate mofetil and increase of steroid led to second remission. The disease remained in complete remission at 60 months after first onset. A 61-year-old woman suffered onset of CNS PTLD 19 years after renal transplantation. After tumor removal, whole brain irradiation was performed. The disease remained in remission at 54 months after onset. Histological examination showed polymorphic-type PTLD in both cases. The first case of polymorphic CNS PTLD was successfully treated by modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[ 8 ] Arita H, et al presented two cases of P-PTLD treated with RI plus steroids and surgery plus irradiation separately. [ 9 ] Velvet AJJ, et al reported a case treated with RI, craniotomy, radiotherapy and rituximab. [ 10 ] The outcomes of these cases are optimistic, but due to the rarity, there is no consensus of optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Arita H, et al presented two cases of P-PTLD treated with RI plus steroids and surgery plus irradiation separately. [ 9 ] Velvet AJJ, et al reported a case treated with RI, craniotomy, radiotherapy and rituximab. [ 10 ] The outcomes of these cases are optimistic, but due to the rarity, there is no consensus of optimal treatment.…”
Section: Discussionmentioning
confidence: 99%